2018
DOI: 10.1038/s41396-017-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Infection dynamics of insecticide-degrading symbionts from soil to insects in response to insecticide spraying

Abstract: Insecticide resistance is a serious concern in modern agriculture, and an understanding of the underlying evolutionary processes is pivotal to prevent the problem. The bean bug Riptortus pedestris, a notorious pest of leguminous crops, acquires a specific Burkholderia symbiont from the environment every generation, and harbors the symbiont in the midgut crypts. The symbiont's natural role is to promote insect development but the insect host can also obtain resistance against the insecticide fenitrothion (MEP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 61 publications
0
61
0
2
Order By: Relevance
“…S1) and only 1 study reported the infection with BCC&P species in overwintering R. pedestris (33). In addition, in insects reared on soil in the laboratory, we occasionally identified infections with PBE Burkholderia as well as Pandoraea, suggesting that colonization of the symbiotic midgut organ is not strictly limited to SBE species (34). Although we revealed that the bacterial sorting organ in the bean bug gut winnows out symbionts from nonsymbionts, only a limited number of bacterial species (i.e., Eschelichia coli, Pseudomonas putida, and Bacillus subtilis) have been tested as nonsymbionts (14).…”
Section: Significancementioning
confidence: 89%
See 1 more Smart Citation
“…S1) and only 1 study reported the infection with BCC&P species in overwintering R. pedestris (33). In addition, in insects reared on soil in the laboratory, we occasionally identified infections with PBE Burkholderia as well as Pandoraea, suggesting that colonization of the symbiotic midgut organ is not strictly limited to SBE species (34). Although we revealed that the bacterial sorting organ in the bean bug gut winnows out symbionts from nonsymbionts, only a limited number of bacterial species (i.e., Eschelichia coli, Pseudomonas putida, and Bacillus subtilis) have been tested as nonsymbionts (14).…”
Section: Significancementioning
confidence: 89%
“…Symbiotic Organ in Coinfection Assays. PBE Burkholderia and Pandoraea species are common bacterial groups in soil environments, and detected frequently with SBE Burkholderia (34,38,39). Given the high infectivity and benefits of PBE and Pandoraea, why do only SBE Burkholderia prevail in field populations of the bean bug?…”
Section: Sbe Burkholderia Always Outcompete Pbe and Pandoraea In The Gutmentioning
confidence: 99%
“…This suggests that horizontal transmission of Burkholderia can occur via enrichment of the symbiont in the local environment by adult insects. While this possibility has been proposed previously (Itoh et al, 2018) to our knowledge this is the first empirical evidence that it can occur in a bug-Burkholderia symbiosis. It seems plausible that horizontal transmission via environmental enrichment also happens in the wild, given the insects' tendency to aggregate.…”
Section: Discussionmentioning
confidence: 64%
“…There are a number of remarkable studies that illustrate the substantial impact of locally adapted microbes on hosts, suggesting that microbes may underlie host adaptation to populations in stressful environments. For example, bean bugs can gain pesticide resistance through acquiring a pesticide degrading soil bacterium, Burkholderia [79][80][81] . Many other hosts utilize their microbiome to detoxify harmful chemicals.…”
Section: Hosts Leverage Locally Adapted Microbesmentioning
confidence: 99%